Relationship between maternal grit and effortful control among 18–21-month-old toddlers - Jung, Awoun; Ishibashi, Mikako; Shinya, Yuta; Itakura, Shoji (Frontiers in Psychology, 2024)
Grit is known to be effective for long-term academic and social success. However, few studies have focused on the role of grit in parenting and its effect on the development of grit in children. Therefore, this study investigated the effect of maternal grit on children's effortful control (EC), which is thought to be a precursor to grit, using parenting as a mediating factor. Participants in the current study were 412 children (age range: 18-21 months, M = 34.67 months, SD = 4.51 months) and their mothers. We assessed maternal grit, parenting style, maternal EC, and child EC, and found that maternal grit, maternal EC, and parenting style were positively correlated with child EC. Furthermore, maternal grit was related to EC in children not only directly, but also indirectly through responsive parenting. Additionally, maternal grit was found to be directly related to child EC only when assessed separately from maternal EC. The current study's findings suggest that maternal grit is directly related to EC in children in a way that differs from the mother's EC in child-rearing situations.